PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING MENGGUNAKAN MEDIA MICROSOFT FRONTPAGE DAN AKTIVITAS BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA KELAS X SMA - Ropinus Sidabutar (Jurnal Guru Kita PGSD, 2020)
Abstract: The Effect of Problem Based Learning Model Using Microsoft Frontpage Media and Learning Activities on Mathematics Learning Outcomes of Class X Senior High School. The purpose of this study was to see (a) the effect of problem based learning using Microsoft Frontpage media on mathematics learning outcomes of high school students, (b) the effect of learning activities on high school students' mathematics learning outcomes, (c) the effect of the interaction between problem based learning. by using Microsoft Frontpage media with learning activities on Mathematics learning outcomes. The population in this study were all class X students at SMA Negeri 1 Sibabangun consisting of 3 classes for the 2019/2020 school year. The sampling technique was carried out by means of purposive sampling. The research sample consisted of the experimental class and the control class. The experimental class was taught by learning problem-based learning with microsoft frontpage media, namely class X-2 and class control taught by learning media microsoft frontpage, namely class X-3. The instruments used in this study were a learning outcome test and a learning activity questionnaire. Student learning outcomes using problem-based learning with Microsoft Frontpage media an average gain of 0.38 is higher than the average gain value of student learning outcomes taught using Microsoft Frontpage media of 0.24. The average gain of learning activities is 0.4. Keywords: Problem Based Learning, Microsoft Frontpage, Learning Activities Abstrak: Pengaruh Model Pembelajaran Problem Based Learning  Menggunakan Media Microsoft Frontpage Dan Aktivitas Belajar Terhadap Hasil Belajar Matematika Kelas X Sma. Tujuan dari penelitian ini adalah untuk melihat (a) pengaruh  pembelajaran  problem based learning dengan menggunakan media Microsoft Frontpage terhadap hasil belajar Matematika siswa SMA, (b) pengaruh aktivitas belajar terhadap hasil belajar Matematika siswa SMA, (c)  pengaruh interaksi antara  pembelajaran problem based learning dengan menggunakan media microsoft  frontpage  dengan  aktivitas  belajar  terhadap  hasil  belajar  Matematika. Populasi dalam penelitian ini yaitu seluruh siswa kelas X di SMA Negeri 1 Sibabangun terdiri dari 3 kelas tahun ajaran 2019/2020. Teknik pengambilan sampel dilakukan dengan cara  purposive sampel.  Sampel  penelitian terdiri  atas kelas eksperimen dan kelas kontrol. Kelas  eksperimen  diajarkan  dengan pembelajaran problem based learning dengan media microsoft frontpage yaitu kelas X-2 dan kelas  kontrol diajarkan dengan pembelajaran media  microsoft frontpage  yaitu  kelas   X-3. Instrumen yang digunakan dalam penelitian ini adalah tes hasil belajar dan kuisioner aktivitas belajar. Hasil belajar siswa menggunakan pembelajaran  problem based learning dengan  media  Microsoft  Frontpage  rata-rata gain sebesar 0,38 lebih tinggi dari nilai rata-rata gain hasil belajar siswa yang diajarkan dengan menggunakan media microsoft frontpage sebesar 0,24. Rata-rata gain aktivitas belajar sebesar 0,4. Keywords : Problem Based Learning, Microsoft Frontpage, Aktivitas Belajar